Factors associated with foreign-educated nurses' willingness to continue working in Japan: a qualitative study - Kazuko Tanaka; Koichi Yoshimura (BMC, 2024)
Abstract Background Japan has been accepting foreign nurse candidates since 2008 under Economic Partnership Agreements (EPAs). As globalisation progresses, nurses from diverse backgrounds are expected to play an active role in the medical field. Using an interview survey, this study examined the factors associated with EPA nurses' willingness to continue working in Japan. Methods We conducted semi-structured interviews from January 2022 to July 2023 with eight EPA nurses and one EPA nurse candidate working in Japan to investigate the factors associated with foreign-educated nurses' willingness to continue working in Japan. The interview guide included items on the status of the daily performance of their duties, what they found pleasurable in their nursing experience in Japan, difficulties they encountered in carrying out their nursing duties, and their expectations of the Japanese staff around them. Data were analysed using thematic analysis. Results From the interview data, seven themes were extracted. To continue working in Japan, it was important for EPA nurses to be able to communicate with patients and colleagues, maintain self-esteem and motivation, be resilient, have support from EPA peers and family members, be accepted by others such as patients and colleagues, and be satisfied with the support they received. Conclusion The EPA nurses experienced many difficulties after becoming nurses and tended to be isolated because of their non-Japanese status. The results suggest that not only support from colleagues and supervisors but also a general understanding of EPA nurses from Japanese society is necessary. As globalisation accelerates, the Japanese nursing field needs to understand the diversity of the nursing profession and build a support system that will enable them to continue to take pride and feel motivated in their work.